Existence of Nontrivial Solutions for Perturbed p-Laplacian Equation in ℝN with Critical Nonlinearity. (24th March 2014) - Zhang, Huixing; Liu, Xiaoqian
Abstract : We consider a perturbed p -Laplacian equation with critical nonlinearity in ℝ N . By using variational method, we show that it has at least one positive solution under the proper conditions.